Identification of Sphingomyelinase on the Surface of Chlamydia pneumoniae: Possible Role in the Entry into Its Host Cells - Tuula A. Peñate Medina; Juha T. Korhonen; Riitta Lahesmaa; Mirja Puolakkainen; Oula Peñate Medina; Paavo K. J. Kinnunen (Interdisciplinary Perspectives on Infectious Diseases)
We have recently suggested a novel mechanism, autoendocytosis, for the entry of certain microbes into their hosts, with a key role played by the sphingomyelinase-catalyzed topical conversion of sphingomyelin to ceramide, the differences in the biophysical properties of these two lipids providing the driving force. The only requirement for such microbes to utilize this mechanism is that they should have a catalytically active SMase on their outer surface while the target cells should expose sphingomyelin in the external leaflet of their plasma membrane. In pursuit of possible microbial candidates, which could utilize this putative mechanism, we conducted a sequence similarity search for SMase. Because of the intriguing cellular and biochemical characteristics of the poorly understood entry of Chlamydia into its host cells these microbes were of particular interest. SMase activity was measured in vitro from isolated C. pneumoniae elementary bodies (EB) and in the lysate from E. coli cells transfected with a plasmid expressing CPn0300 protein having sequence similarity to SMase. Finally, pretreatment of host cells with exogenous SMase resulting in loss plasma membrane sphingomyelin attenuated attachment of EB.